Reforms of Environmental Policies in the Presence of Cross-border Pollution and Two-stage Clean-up - Panos Hatzipanayotou; Sajal Lahiri; Michael S. Michael (Center for Economic Studies and ifo Institute (CESifo), 2002)
We construct a two-country model where pollution from production is transmitted across borders. Pollution abatement is undertaken sequentially by private producers and the public sector. We characterize the Nash optimal levels of the policy instruments in the two countries: emission taxes and funds allocated for public abatement activities. We examine the implications of a number of multilateral policy reforms. One of our findings is that the magnitude of the beneficial e.ect of a reform depends on the scope of the reform, and if it is restricted to a subset of policy instruments, then the efficacy of environmental policy reform can be greatly undermined.
Keywords: 330; cross-border pollution; private pollution abatement; public pollution abatement; multilateral policy reform.